Effective adsorption of AuCl4− by functionalized D301 resin: kinetics, isotherms and selectivity. Issue 9 (15th July 2020) - Xue, Xiao-Yan; Li, Hu-Fei; Wang, Yong; An, Fu-Qiang; Hu, Tuo-Ping; Gao, Jian-Feng
Abstract: Two novel adsorbents (AGD301 and ArgD301) were successfully prepared through ring-opening reaction. The adsorption performance and recognition selectivity of AGD301 and ArgD301 towards AuCl4 − were studied by batch adsorption experiments. The results showed that adsorption time, pH, temperature and solution concentration had a significant influence on the adsorption performance. At 298 K and pH of 2, the equilibrium adsorption capacity of AGD301 and ArgD301 towards AuCl4 − could reach 400.75 and 451.67 mg·g −1, respectively. In addition, AGD301 and ArgD301 possessed excellent selectivity and good reusability. Graphical Abstract: